Social Movements and Sexual Citizenship in Southern Europe - Santos, Ana Cristina (2013)
This book explores the relationship between social movements, sexual citizenship and change in Southern Europe. Providing a comparative analysis about LGBT issues in Italy, Spain and Portugal, it discusses how activism can generate legal, political and cultural impact in post-dictatorial, Catholic and EU-focused countries.